Food-related behaviours among individuals with overweight/obesity and normal body weight - Anna Brytek-Matera; Kamila Czepczor-Bernat; Dominik Olejniczak (Nutrition Journal, 2018)
Abstract Background Emotional eating is a factor associated with a negative body image and other problematic eating behaviours. In this context little is known about differences between individuals with overweight and obesity and those with normal body weight. The main aim of the study was to evaluate the role of emotional eating in the relationship between the desire to consume chocolate and the wish to avoid social situations related to food and body exposures. For this purpose, we tested the direct, indirect and buffer effects. In addition, we used moderated mediation by introducing snacking into the model. Methods The study included 123 outpatients with excessive body weight and 123 individuals with normal weight. The mean of body mass index (BMI) in the first group was 30.19 kg/m2 (SD = 4.37) and, in the second, it was 23.02 kg/m2 (SD = 1.20). The Three-Factor Eating Questionnaire, the Attitudes to Chocolate Questionnaire and the Body Image Avoidance Questionnaire were used. Results Results show that in all individuals, the greater emotional eating is, the greater the desire for chocolate consumption and avoidance of social situations related to food and body exposures are. In addition, the desire for chocolate consumption are positively associated with avoidance of social situations related to food and body exposures in both group. Among individuals with excessive and normal body weight, emotional eating is a significant mediator in the relationship between desire for chocolate consumption and avoidance of social situations related to food and body exposures. However, it does not moderate the relationship between these variables. Outcomes show that there is a significant model of moderated mediation of the link between social situation–avoidance related to food and body exposure and the desire to consume chocolate through emotional eating, moderated by snacking among individuals with normal body weight. A similar effect has not been discovered in the group with excessive body weight. Conclusion The presented results show that among people with varied BMI categories, emotional eating is connected to craving chocolate and avoidance of social situations related to food and body exposure that plays only the role of mediation. In addition, snacking is crucial for this relationship among the group with normal body weight.